The Prophetic System: Principles, Evolution, and Impact on Modern Societies (A Scholarly and Research Study) - Mehreen Bilal, D/o Nazir Shah; Associate Professor Dr. Naseem Akhter (Corresponding Author) (Journal of Religion and Society, 2025)
The Prophetic social system introduced by Prophet Muhammad ﷺ presents a comprehensive model of justice, equity, spirituality, and social harmony. Rooted in divine revelation (Wahi), it emphasizes collective responsibility, protection of individual rights, and moral integrity across all segments of society. This system not only provided solutions to the issue of its own time but also laid down universal principal that remain timeless and relevant. This study compares the prophetic model with modern Western societies, which are largely grounded in secularism, individualism, and materialism. The research highlights how the absence of spiritual and moral foundations in modern systems has led to social fragmentation, family disintegration, and inner human unrest. By contrast, the prophetic system strengthens familial bonds, promotes social justice, and balances individual freedom with community welfare. The findings indicate that the implementation of Prophetic values such as mutual respect, accountability, equity, and compassion can significantly contribute to the moral revival of modern societies. This paper concludes that integrating these values into contemporary social structures is not only possible but essential for sustainable peace and coexistence in an increasingly divided world. Keywords: Prophetic social system, Islamic Society, Modern Societies, Social Justice in Islam, Western Individualism, Divine Revelation (Wahi), Moral Values in Islam, Spiritual Crisis, Comparative Social Systems, Sustainable Society.